REINFORCING EFL YOUNG LEARNERS’ VOCABULARY THROUGH SCRABBLE GAME - Yusran Sultan; Andi Hamzah Fansury; Restu Januarty (Teaching English as a Foreign Language Overseas Journal, 2022)
The objectives of the research were to know the use of scrabble game can reinforce EFL Young Learners vocabulary. The writer was applied pre-experimental with one group pre-test and post-test. This research was conducted at SMPN 35 Makassar sub-district of Biringkanaya, Makassar city. In this research, the population was the seven grade students of SMPN 35 Makassar. The total numbers of population were 240 students. The researcher was used total sampling technique. The total number of samples was 30 students from class VII-1. In analyzing the numerical data, the writer used SPSS for windows. After conducted the research, the writer concludes that the use of Scramble Game in teaching English vocabulary enriches the students’ vocabulary; it is proved by the mean score of the students in pre-test and posttest. The mean score of the pre-test before the treatment was 57.40 and after the treatment the students gained score 74.67. The t-test of the students’ vocabulary achievement in posttest was smaller than ?. The researcher found that the p-value (probability value) was lower than ? (0.00 < 0.05) and the degree of freedom was 29. The t-test value of pre-test and post-test was remarked significantly different. It indicated that the alternative hypothesis (H1) was accepted and, of course, the null hypothesis (H0) was rejected.o learn autonomously and it is compulsory subject from the school.